2020
DOI: 10.1186/s12941-020-00362-2
|View full text |Cite
|
Sign up to set email alerts
|

Plasma CRP level is positively associated with the severity of COVID-19

Abstract: Aims: The coronavirus disease 2019 is characterized as highly contagious and deadly; however there is no credible and convenient biomarker to predict the severity of the disease. The aim of the present study was to estimate whether the CRP level is able to act as a marker in indicating the severity of COVID-19.Methods: Patients who complained cough or chest pain with or without fever were enrolled after laboratory confirmed of SARS-CoV-2 viral nucleic acid via qRT-PCR. Chest computed tomography (CT) was then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
265
6
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 288 publications
(314 citation statements)
references
References 9 publications
34
265
6
9
Order By: Relevance
“…Higher CRP level has been reported as positively related to the severity of lung injury and COVID-19 severity by other researchers (12,13). However, in our study, no signi cant correlation between plasma CRP level and the risk of initial GI involvement has been found in this study ( Table 1).…”
Section: Correlation Between Clc and Initial Gi Involvementcontrasting
confidence: 74%
“…Higher CRP level has been reported as positively related to the severity of lung injury and COVID-19 severity by other researchers (12,13). However, in our study, no signi cant correlation between plasma CRP level and the risk of initial GI involvement has been found in this study ( Table 1).…”
Section: Correlation Between Clc and Initial Gi Involvementcontrasting
confidence: 74%
“…Age, comorbidities, c-reactive protein, albumin, cytokine, lactate dehydrogenase, D-dimer, albumin, platelet, lymphocyte, neutrophil, smoking, cough, expectoration, chest pain, dyspnea, CT manifestations, et al, have been reported to be associated with the severity of COVID-19 in some small studies in China, [15][16][17][18][19][20][21] and other countires. 13,22,23 Jiangsu, a province in China over 600 km from Hubei without common geographical borders and 80 million population, reported over 600 patients infected with COVID-19.…”
mentioning
confidence: 99%
“…The association of CRP with poor outcomes in COVID-19 has already been reported by Li et al, Feng et al, Chen et al and Wang. 7,8,19,20 Research suggests that CRP is one of the most important biomarkers to predict the prognosis of COVID-19. 10 The serum ferritin increased from the baseline in survivors and non-survivors, but the rise in both groups was not signi cant.…”
Section: Resultsmentioning
confidence: 99%
“…6 Apart from gender, age, blood groups, and co-morbidities, a plethora of laboratory markers have been investigated to predict the course and outcome of the disease. [7][8][9][10] Infection with SARS CoV-2 leads to the release of cytokines and chemokines from monocytes, lymphocytes and macrophages resulting in an in ammatory response. 11 The common laboratory parameters which are supposed to be linked with worse outcome in COVID-19 include C-reactive protein (CRP), interleukin-6 (IL-6), D-dimer, brinogen, Lactate Dehydrogenase (LDH), Cardiac Troponin, lymphocyte count, serum ferritin, serum amyloid A (SAA) and erythrocyte sedimentation rate (ESR).…”
Section: Introductionmentioning
confidence: 99%